Structural characterization of novel comb-like branched α-d-glucan from Arca inflata and its immunoregulatory activities in vitro and in vivo. Issue 10 (25th September 2019) - Li, Chunlei; Peng, Dan; Huang, Weijuan; Ou, Xiaozheng; Song, Liyan; Guo, Zhongyi; Wang, Haoran; Liu, Wanying; Zhu, Jianhua; Yu, Rongmin
Abstract : In the current study, we identified and characterized a novel water-soluble polysaccharide (JNY2PW) with significant immunoregulatory effects and no apparent overall toxicity. Abstract : In the current study, we identified and characterized a novel water-soluble polysaccharide (JNY2PW) with significant immunoregulatory effects and no apparent overall toxicity. JNY2PW, which was isolated from Arca inflata, belongs to a novel class of α-glucans with a molecular weight of 5.25 × 10 7 Da. Its backbone is composed of (1 → 4)-linked α-d -glucopyranosyl residues and a single (1 → 6)-α-d -glucopyranosyl branched unit for every five α-d -glucopyranosyl residues, showing a comb-like α-d -glucan with intensive short branches. Using in vitro models, we demonstrated that JNY2PW exerts significant immunoregulatory effects by promoting the production of nitric oxide, interleukin-6, and tumor necrosis factor α. The pathway involves the activation of the TLR4-MAPK/NF-κB signaling cassette in murine RAW264.7 macrophages. In an in vivo immunosuppressive mice model induced by cyclophosphamide treatment, we found that the JNY2PW treatment produced good antitumor activity, comparable to that of chemotherapy by doxycycline in murine breast carcinoma 4T1-bearing mice, but devoid of any observable side effects ( e.g. weight loss) related with doxycycline treatment. The anti-tumor mechanism of JNY2PW may involve an overall enhancement in the immune responses of the mice to tumors. These results indicate that JNY2PW possesses potential as an adjuvant to existing chemotherapy and current immune-oncology treatment.